(438) Labour Productivity in Planning - Manfred Engert (معهد التخطيط القومى, 2026)
This study examines the concept of labour productivity and its central role in economic planning and development processes, emphasizing the significance of human resources as a major determinant of economic growth and efficient resource utilization. The study is based on the assumption that labour efficiency is influenced not only by the quantity of labor employed but also by skills, managerial organization, technological development, and production methods implemented across economic sectors. The study presents a theoretical framework of labour productivity by defining productivity as the relationship between output generated and inputs utilized in the production process. It distinguishes between partial and total productivity measures and highlights the importance of labour productivity indicators as tools for evaluating economic performance and efficiency in resource utilization. Furthermore, the study investigates the major factors affecting labour productivity, including educational attainment, vocational training, work experience, managerial quality, technological progress, and broader economic and social conditions. These factors are analyzed in terms of their influence on workforce efficiency and long-term economic growth patterns. Within the context of economic planning, the study explains the importance of incorporating labour productivity indicators into development planning processes. Such indicators contribute to forecasting labor force requirements, guiding investments toward more productive sectors, and improving the allocation of economic resources. The study concludes that increasing labour productivity constitutes a strategic instrument for achieving sustainable economic development. Effective planning policies should therefore emphasize human capital development, educational and training improvements, and the adoption of advanced managerial and technological practices aimed at increasing economic efficiency and strengthening long-term growth performance.